Pasantía enfocada en el planteamiento e implementación de estrategias para mitigar riesgos laborales a los trabajadores de los proyectos de BJR en Duitama Boyacá - Rodriguez Tavera, Laura Daniela (Universidad Antonio Nariño, 2022)
This work is carried out during the development of the internship in the company Arquitectura Diseño y Construcción BJR of Duitama Boyacá as a degree project, in order to contribute to a safety plan that mitigates the risks to which workers are exposed in a work, taking into account that construction is one of the sectors where work accidents occur the most, which is why we wanted to intervene in it. This document describes the support in the planning and development of strategies for the occupational health and safety management system, where three phases were proposed, consisting of information gathering, diagnosis, hazard identification and risk assessment. where the established guidelines, standards and methodologies were taken as a reference to apply a response plan to the hazards found in each phase of the project; in order for both employers and employees to act appropriately in any emergency situation, improving the well-being and quality of life of workers.